Molecular and phylogenetic characterization based on the complete genome of a virulent pathotype of Newcastle disease virus isolated in the 1970s in Brazil - Fernandes, Camila C. [UNESP]; Varani, Alessandro M. [UNESP]; Lemos, Eliana G. M. [UNESP]; Miranda, Vitor Fernandes O. de [UNESP]; Silva, Ketherson R. [UNESP]; Fernando, Filipe S. [UNESP]; Montassier, Maria F. S. [UNESP]; Montassier, Helio J. [UNESP] (Elsevier B.V., 2014)
Newcastle disease (ND) is caused by the avian paramyxovirus type 1 (APMV-1) or Newcastle disease virus (NDV) that comprises a diverse group of viruses with a single-stranded, negative-sense RNA genome. ND is one of the most important diseases of chickens, because it severely affects poultry production worldwide. In the 1970s, outbreaks of virulent ND were recorded in Brazil, and the strain APMV-1/Chicken/Brazil/SJM/75 (SJM) of NDV was isolated. This strain was characterized as highly pathogenic for chickens but not pathogenic for other bird species. Here we present the complete genome of NDV strain SJM and investigate the phylogenetic relationships of this virus with other NDV strains in terms of genome and proteins composition, as well as characterizing its evolution process. The NDV strain SJM is categorized as a velogenic virus and the complete genome is 15,192 nucleotides in length, consisting of six genes in the order 30-NP-P-M-F-HN-L-5'. The presence of the major pathogenic determinant of NDV strains (R-112-R-Q-K-R down arrow F-117) was identified in the Fusion protein of the NDV strain SJM. In addition, phylogenetic analysis classified the NDV strain SJM as a member of class II, genotype V, and indicates that this virus help us in the understanding of the evolutionary process of strains belonging to this genotype. This study contributes to the growing interest involving the characterization of NDV isolates to improve our current understanding about the epidemiology, surveillance and evolution of the pathogenic strains. (C) 2014 The Authors. Published by Elsevier B. V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/3.0/).
Keywords: Newcastle disease virus; APMV-1; Virulent strain; Complete genome; Phylogenetic analysis